Implementation of Vocational Technology Education Philosophy in Competency-Based Curriculum Design: A Systematic Literature Review - Andi Putra; Nizwardi Jalinus; Ernawati Ernawati; Fadhilah Fadhilah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
Vocational technology education plays a strategic role in preparing a skilled workforce that is competent in accordance with industry needs. This article aims to analyze the implementation of vocational technology education philosophy in competency-based curriculum design through a systematic literature review approach. This study uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method by analyzing 35 journal articles from various academic databases published between 2015 and 2024. The review results show that the philosophy of vocational technology education is based on three main principles: work-based learning, industry linkage, and holistic competency development that includes cognitive, affective, and psychomotor aspects. The implementation of this philosophy in competency-based curricula is realized through: (1) the integration of theory and practice learning with a balanced ratio; (2) collaboration between educational institutions and industry in formulating competency standards; (3) an authentic assessment system that measures overall competency mastery; and (4) learning that is responsive to technological developments and labor market demands. This study recommends the need to strengthen synergy between stakeholders, continuously update the curriculum, and improve the capacity of educators to optimize the implementation of the philosophy of vocational technology education in competency-based curricula.